Finding Opportunities from Surprises and Failures. Development of Rhodium-Stabilized Donor/Acceptor Carbenes and their Application to Catalyst-Controlled C—H Functionalization - Davies, Huw M. L. (J Org Chem, 2019)
Catalyst-controlled C—H functionalization by means of the C—H insertion chemistry of rhodium carbenes has become a powerful synthetic method. The key requirements for the development of this chemistry are donor/acceptor carbenes and the chiral dirhodium tetracarboxylate catalysts. This perspective will describe the stages involved in developing this chemistry and illustrate the scope of the donor/acceptor carbene C—H functionalization.